Sense and limits of the Fichtean project of a closed commercial State - Arrese Igor, Héctor Oscar (2018)
In this paper, I intend to determine the objectives and limitations of the project developed by Fichte in The Closed Commercial State. In order to achieve these aims, I first identify the problems that are left open in the cosmopolitan right of the Foundations of the Natural Right, in particular by virtue of the assumption of universal egoism. In this way, I seek to understand the project of The Closed Commercial State as an attempt to solve these outstanding issues. Thereafter, I reconstruct the central argumentations of the later text in order to make its architecture clear, according to its primary objectives. Finally, I consider the problem of the viability of this project, taking into account the lack of a moral education for the citizens focused on certain moral and psychological dispositions, which should reduce the greed for superfluous goods.